Early Enteral Versus Total Parenteral Nutrition in Patients Undergoing Pancreaticoduodenectomy: A Randomized Multicenter Controlled Trial (Nutri-DPC). Issue 5 (November 2016) - Perinel, Julie; Mariette, Christophe; Dousset, Bertrand; Sielezneff, Igor; Gainant, Alain; Mabrut, Jean-Yves; Bin-Dorel, Sylvie; Bechwaty, Michel El; Delaunay, Dominique; Bernard, Lorraine; Sauvanet, Alain; Pocard, Marc; et al.
Abstract : Objectives: The aim of this study was to compare nasojejunal early enteral nutrition (NJEEN) with total parenteral nutrition (TPN), after pancreaticoduodenectomy (PD), in terms of postoperative complications. Background: Current nutritional guidelines recommend the use of enteral over parenteral nutrition in patients undergoing gastrointestinal surgery. However, the NJEEN remains controversial in patients undergoing PD. Methods: Multicenter, randomized, controlled trial was conducted between 2011 and 2014. Nine centers in France analyzed 204 patients undergoing PD to NJEEN (n = 103) or TPN (n = 101). Primary outcome was the rate of postoperative complications according to Clavien-Dindo classification. Successful NJEEN was defined as insertion of a nasojejunal feeding tube, delivering at least 50% of nutritional needs on PoD 5, and no TPN for more than consecutive 48 hours. Results: Postoperative complications occurred in 77.5% [95% confidence interval (95% CI) 68.1–85.1] patients in the NJEEN group versus 64.4% (95% CI 54.2–73.6) in TPN group ( P = 0.040). NJEEN was associated with higher frequency of postoperative pancreatic fistula (POPF) (48.1% vs 27.7%, P = 0.012) and higher severity (grade B/C 29.4% vs 13.9%; P = 0.007). There was no significant difference in the incidence of post-pancreatectomy hemorrhage, delayed gastric emptying, infectious complications, the grade of postoperative complications, and the length of postoperative stay. A successful NJEEN was achieved in 63% patients. In TPN group, average energy intake was significantly higher ( P < 0.001) and patients had an earlier recovery of oral feeding ( P = 0.0009). Conclusions: In patients undergoing PD, NJEEN was associated with an increased overall postoperative complications rate. The frequency and the severity of POPF were also significantly increased after NJEEN. In terms of safety and feasibility, NJEEN should not be recommended.